ANALISIS PENDAPATAN PETANI TERHADAP PEREKONOMIAN MASYARAKAT DI DESA ADAT ASAK - Ni Wayan Ari Sudiartini; Ni Putu Santika Dewi (Forum Manajemen STIMI Handayani Denpasar, 2020)
The purpose of the study, among others, is to analyze the income of farmers producing rice for the community’s economy. The study was conducted on 6 sample farmers in the Asak Adat Village in the Karangasem District, Karangasem Regency, Bali. Data collection is done by interview and documentation techniques. The analytical tool used is income analysis. The results showed that the results calculated by the method of analysis of farm income according to Soekarwati (2006: 58). Shows that the income of rice farmers in terms of the average yield per acre is Rp. 186,160 and the average income per 3 months is only Rp. 3,210,000 which is far below the minimum wage, so the results of this study show that farmers who earn below the minimum wage are not sufficient for their daily needs and cannot even guarantee long-term or future life. The factors of area of arable land, the amount of effective labor, the amount of fertilizer, the amount of pesticides, the experience of farmers in trying to farm, the distance of the farmer’s house to arable land, and the irrigation system have a very significant effect on increasing the production of lowland rice, whereas, the experience of farmers has no effect ( non significant) to increase paddy rice production.